Design of PC-based quantitative split charging device for hydrogen isotope elemental gases. (20th July 2017) - Cheng, Honghui; Xi, Chenyu; Liu, Jingjing; Han, Xingbo; Wang, Yu; Liu, Wei
Abstract: A quantitative split charging device for hydrogen isotope elemental gases in the operation ranges of 10 −5 Pa − 6 bar, 15–40 °C, and 10–500 sccm, controlled by a personal computer (PC) on the workbench of LabVIEW software, was carefully designed and constructed. In the device, volumetric charging mode and flow-controller charging mode can be adopted according to the molar quantity of split charging. The leakage rate and the quantitative split charging accuracy of the set-up were evaluated systemically. According to the experimental results of quantitative split charging from our device and mass comparator, this apparatus is well designed and assembled, and can guarantee 0.001 g quantitative split charging accuracy in the two charging modes. Highlights: A novel quantitative split charging device for hydrogen gases was developed. Two charging modes could be adopted in the device. The leakage rate of the device was about 2.3 × 10 −12 g H2 /s. The device could guarantee 0.001 g quantitative split charging accuracy.